THE EFFECT OF TRUST AND INFORMATION QUALITY ON THE DECISION TO PURCHASE AIRLINE TICKETS ON E-COMMERCE TRAVELOKA (Case Study: Traveloka Users In The District Of Manokwari) - Chindi Mellani; Louis Soemadi Bopeng; Makarius Bajari (Cakrawala Management Business Journal, 2019)
In line with the increasing number of internet users, many companies have changed the structure of public spending based on online conditions. The purpose of this study is to analyze and test the effect of trust and information quality on the decision to purchase airline ticket on e-commerce Traveloka. This research is a quantitative, according to its implantation, associative research. The sampling method used is non-probability sampling with purposive sampling technique. The analysis that has been conducted by the researcher found that: (1) the trust variable (X1) partially has no effect on the purchasing decision (Y) The confidence variable has a value of t count 1.616 which is smaller than the t table value of 1.991 (1.616 <1.991) and significance value 0.110 is greater than the value of ∝ (alpha) which is 0.05 (0.110> 0.05). (2) information quality variable (X2) partially affects the purchasing decision (Y) Information quality variable has a t value of 4.375 which is greater than the t table value of 1.991 (4.375> 1.991) and a significance value of 0.000 is smaller than the value alpha is 0.05 (0.000 <0.05). (3) the trust variable (X1) and the information quality variable (X2) together (simultaneously) affect the purchasing decision variable (Y) the significance value of F is 0,000 with an error level of 0.5 which means the significance value of F is 0.05 smaller (0,000 <0,05).